2014
DOI: 10.4038/cmj.v47i1.6417
|View full text |Cite
|
Sign up to set email alerts
|

Viral myositis caused by Epstein-Barr virus (EB virus) in children

Abstract: We studied the aetiological agents responsible for causing a febrile illness associated with severe pain in calf muscles in children. All children presenting with a short febrile illness with difficulty in walking due to severe pain in the calf muscles were included in our study, done in the private and public sectors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Concerning the causative agents, viral myositis has been reported following infections with influenza‐B , influenza‐A , parainfluenza‐1 , parvoviruses , HTLV‐1 , Epstein‐Barr virus , arboviruses (e.g., dengue myositis) , adenovirus , coxsackie , herpes , human immunodeficiency virus‐1 (HIV‐1) , or chickenpox . Most frequently myositis is due to infection with the influenza or parainfluenza virus .…”
Section: Resultsmentioning
confidence: 99%
“…Concerning the causative agents, viral myositis has been reported following infections with influenza‐B , influenza‐A , parainfluenza‐1 , parvoviruses , HTLV‐1 , Epstein‐Barr virus , arboviruses (e.g., dengue myositis) , adenovirus , coxsackie , herpes , human immunodeficiency virus‐1 (HIV‐1) , or chickenpox . Most frequently myositis is due to infection with the influenza or parainfluenza virus .…”
Section: Resultsmentioning
confidence: 99%
“…Although many infective agents including respiratory syncytial virus, parainfluenza virus, parvovirus, adenovirus, herpes simplex virus, Epstein-Barr virus, cytomegalovirus, mycoplasma, and rotavirus causing URIs can cause myositis, the disease is most often caused by influenza viruses. 10,12,[14][15][16] Recently, it has been reported that BACM develops after an influenza A (H1N1) virus infection. 7 In 2000 to 2001, it was reported that myositis had developed after an URI in 197 children.…”
Section: Discussionmentioning
confidence: 99%